2017
DOI: 10.1007/s10802-017-0332-3
|View full text |Cite
|
Sign up to set email alerts
|

Sympathetic Under-Arousal and Externalizing Behavior Problems in Children with Autism Spectrum Disorder

Abstract: Children with autism spectrum disorder (ASD) commonly exhibit co-occurring externalizing behavior problems, which can impede learning opportunities and contribute significantly to caregiver stress. Substantial theory and research has linked under-arousal of the sympathetic nervous system to increased externalizing problems in children without ASD, but under-arousal has not been considered as an explanatory mechanism for individual differences among children with ASD. We tested the notion that lower electroderm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
42
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 38 publications
(51 citation statements)
references
References 84 publications
9
42
0
Order By: Relevance
“…However, recent evidence suggests that certain SNS–PNS profiles may sensitize children to parenting effects [Abaied et al, ], and it is possible that different types of parental reactions might be more or less beneficial depending upon children's underlying psychophysiology. For instance, parenting that promotes increased task engagement while providing effective behavioral contingencies may be particularly important for reducing comorbid behavior problems in children with ASD exhibiting low SNS arousal tendencies [Baker, Fenning, Erath, et al, ]. In contrast, reducing parental criticism and harsh discipline may be especially helpful for children with ASD with high SNS or PNS reactivity [Baker, Fenning, Howland, & Huynh, ; Baker et al, ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…However, recent evidence suggests that certain SNS–PNS profiles may sensitize children to parenting effects [Abaied et al, ], and it is possible that different types of parental reactions might be more or less beneficial depending upon children's underlying psychophysiology. For instance, parenting that promotes increased task engagement while providing effective behavioral contingencies may be particularly important for reducing comorbid behavior problems in children with ASD exhibiting low SNS arousal tendencies [Baker, Fenning, Erath, et al, ]. In contrast, reducing parental criticism and harsh discipline may be especially helpful for children with ASD with high SNS or PNS reactivity [Baker, Fenning, Howland, & Huynh, ; Baker et al, ].…”
Section: Discussionmentioning
confidence: 99%
“…Lower EDA-R has been identified as a risk factor for externalizing problems, with this association thought to be mediated by a reduced physiological sensitivity to threat or socialization efforts [Beauchaine et al, 2007]. A direct link between lower EDA-R in compliance contexts and externalizing behavior problems has been replicated in children with ASD, but this effect may be open to moderation when EDA-R is measured under conditions with less emphasis on compliance [Baker, Fenning, Erath, et al, 2018]. Results of the present study suggested an association between lower EDA-R during a challenge task and externalizing problems at lower and moderate levels of RSA-R.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations